The color of money - Tevis, Walter (London : Weidenfeld & Nicolson, 1984)
After 20 years of hibernation, former pool champion "Fast" Eddie Felson is now ready to regain the skills needed to compete in a world of pool that has changed dramatically since he left it behind. "The Color of Money" is the source of the 1986 film starring Paul Newman in the role he had originated in "The Hustler."
Originally published: New York, NY : Warner Books, 1984.
Keywords: Pool (Game) -- Fiction; Pool (Game); Novels; Fiction